PERAN OFFICE OF THE HIGH COMMISSIONER FOR HUMAN RIGHTS (OHCHR) MENYELAMARKAN KEKERASAN ETNIS MUSLIM ROHINGYA DI MYANMAR (2012-2014) - Rizki, Rika; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains the role of the Office of the High Commissioner for Human Rights (OHCHR) in the ethnic conflict that accurred in Rakhine State, Myanmar, between Arakanese Buddhist and Rohingya Muslims in mid 2012. The violence against the Rohingya Muslim minority has a very long felt. They were not granted citizenship and be oppressed minorities. They also got discrimination in various fields, economic, political and social.The research applies qualitative methods, and case study in this research the data collected through library research, literature studies, official documents, academic journal, and mass media.Therefore, as a form of international concern as the OHCHR human rights bodies providing assistance to the Rohingya Muslim minorities. One of them by sending special rappourter to the country of myanmar for communicate with the government Myanmar.Keywords: Human Rights, Citizenship, Ethnic Minorities, OHCHR, Government